Hydrogel-coated feed spacers in two-phase flow cleaning in spiral wound membrane elements: A novel platform for eco-friendly biofouling mitigation. (15th March 2015) - Wibisono, Yusuf; Yandi, Wetra; Golabi, Mohsen; Nugraha, Roni; Cornelissen, Emile R.; Kemperman, Antoine J.B.; Ederth, Thomas; Nijmeijer, Kitty
Abstract: Biofouling is still a major challenge in the application of nanofiltration and reverse osmosis membranes. Here we present a platform approach for environmentally friendly biofouling control using a combination of a hydrogel-coated feed spacer and two-phase flow cleaning. Neutral (polyHEMA-co-PEG10 MA), cationic (polyDMAEMA) and anionic (polySPMA) hydrogels have been successfully grafted onto polypropylene (PP) feed spacers via plasma-mediated UV-polymerization. These coatings maintained their chemical stability after 7 days incubation in neutral (pH 7), acidic (pH 5) and basic (pH 9) environments. Anti-biofouling properties of these coatings were evaluated by Escherichia coli attachment assay and nanofiltration experiments at a TMP of 600 kPag using tap water with additional nutrients as feed and by using optical coherence tomography. Especially the anionic polySPMA-coated PP feed spacer shows reduced attachment of E. coli and biofouling in the spacer-filled narrow channels resulting in delayed biofilm growth. Employing this highly hydrophilic coating during removal of biofouling by two-phase flow cleaning also showed enhanced cleaning efficiency, feed channel pressure drop and flux recoveries. The strong hydrophilic nature and the presence of negative charge on polySPMA are most probably responsible for the improved antifouling behavior. A combination of polySPMA-coated PP feed spacers and two-phase flow cleaning therefore is promising and an environmentally friendly approach to control biofouling in NF/RO systems employing spiral-wound membrane modules. Graphical abstract: Highlights: A novel platform approach for eco-friendly biofouling mitigation is presented. Hydrogel-coated feed spacers and two-phase flow cleaning showed a good biofouling control. The surface charge plays an important role on the anti biofouling behavior. The coatings are stable after 7 days incubation in neutral, acidic and basic environments.